2022
DOI: 10.1001/jamanetworkopen.2021.42069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Therapeutic Aquatic Exercise vs Physical Therapy Modalities for Patients With Chronic Low Back Pain

Abstract: IMPORTANCE Therapeutic aquatic exercise is frequently offered to patients with chronic low back pain, but its long-term benefits are unclear.OBJECTIVE To assess the long-term effects of therapeutic aquatic exercise on people with chronic low back pain. DESIGN, SETTING, AND PARTICIPANTSThis 3-month, single-blind randomized clinical trial with a 12-month follow-up period was performed from September 10, 2018, to March 12, 2019, and the trial follow-up was completed March 17, 2020. A total of 113 people with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…Proper exercise can improve the physiological function of various organs of the body and improve the overall morphology of the body ( Benedetti et al, 2018 ). In addition, exercise can also relieve pain ( Belavy et al, 2021 ; Zheng et al, 2021 ; Peng et al, 2022 ; Wu et al, 2022 ). For OA patients, ladder treatment is generally adopted, starting with basic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Proper exercise can improve the physiological function of various organs of the body and improve the overall morphology of the body ( Benedetti et al, 2018 ). In addition, exercise can also relieve pain ( Belavy et al, 2021 ; Zheng et al, 2021 ; Peng et al, 2022 ; Wu et al, 2022 ). For OA patients, ladder treatment is generally adopted, starting with basic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high morbidity and family burden of DPNP, an increasing number of studies have been involved in the field of DPNP, and relevant literature has been published in academic journals. Some studies have explored the mechanisms of pain relief by non-pharmacological interventions ( Zheng et al, 2021 ; Peng et al, 2022 ; Wu et al, 2022 ). However, only a few large-scale systematic global reviews of DPNP have been published ( Çakici et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various exercises have been recommended to mitigate chronic pain, and different types of exercise produce different analgesic effects. [19][20][21][22][23] A quasi-experiment found that healthy women experienced an increase in PPTs after completing knee extension strength training, and the effect returned to baseline levels after 20-minute exercise even if the test sites were far from the area of active muscles. 24 Jones et al recruited 16 healthy adults to complete 20 minutes of moderateintensity aerobic exercise on a cycle ergometer, and the results showed a substantial increase in PPTs but not in heat pain thresholds after exercise.…”
Section: Introductionmentioning
confidence: 99%